Thermal shock resistant and corrosion resistant honeycomb ceramic and preparation method thereof

By adding composite additives of samarium oxide and zirconium oxide to honeycomb ceramics, the problems of corrosion and thermal shock damage in high-temperature environments are solved, and the high corrosion resistance and thermal shock resistance of ceramics are achieved, extending service life and reducing costs.

CN119528600AActive Publication Date: 2025-02-28CENT SOUTH UNIV +1

Patent Information

Application Number
CN202411624817.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-28
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

Existing honeycomb ceramics are susceptible to corrosion and thermal shock damage in high temperature environments, resulting in aging of materials, decreasing strength and shortening of service life.

Method used

By adding a composite additive of samarium oxide and zirconium oxide to the base powder of honeycomb ceramics, the thermal shock resistance and corrosion resistance of the ceramics are adjusted.

Benefits of technology

It significantly improves the acid and alkali corrosion resistance and thermal shock resistance of honeycomb ceramics, extends its service life, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528600A_ABST
    Figure CN119528600A_ABST
Patent Text Reader

Abstract

The invention discloses a thermal shock resistant and corrosion resistant honeycomb ceramic and a preparation method thereof. The honeycomb ceramic comprises basic powder and a composite additive, the composite additive comprises samarium oxide and zirconium oxide, wherein the addition amount of the samarium oxide is 1-9 wt% of that of the basic powder, and the addition amount of the zirconium oxide is 1-9 wt% of that of the basic powder. The acid and alkali corrosion resistance of the honeycomb ceramic is improved by adding samarium oxide, meanwhile, the thermal shock resistance of the ceramic is improved by adding zirconium oxide, deformation generated in the sintering process of the ceramic is buffered, and therefore the thermal shock resistant and corrosion resistant honeycomb ceramic is obtained, and the corrosion resistance of the ceramic is synchronously improved through the synergistic interaction effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of honeycomb ceramics, in particular to a honeycomb ceramic resistant to thermal shock and corrosion and a preparation method thereof. Background Art

[0002] Honeycomb ceramics are widely used in automobile exhaust purification, industrial waste gas treatment and other fields. They can be used as a three-way catalytic converter carrier to reduce harmful substances in automobile exhaust, and can also be used in industrial waste gas treatment equipment to reduce harmful gas emissions. In actual applications, waste gas / tail gas often contains acidic / alkaline gases such as sulfur dioxide, nitrogen oxides and ammonia. Under high temperature conditions, the corrosive substances generated by these gases will gradually corrode honeycomb ceramics, causing material aging, strength loss and structural damage, significantly shortening its service life. In addition, honeycomb ceramics with poor thermal shock resistance may suffer thermal shock damage or high-temperature creep when working in a high-temperature environment, which will also affect its performance and service life.

[0003] Studies have shown that by improving the raw material formula of honeycomb ceramics, the thermal shock resistance and corrosion resistance of ceramic materials can be effectively improved. The Chinese patent application with publication number CN117362070A discloses a honeycomb ceramic thermal storage body and a preparation method thereof, wherein the honeycomb ceramic thermal storage body includes a base powder and a rare earth additive; wherein the rare earth additive is added in an amount of 1-17wt% of the base powder, and the rare earth additive includes at least one of cerium oxide, lanthanum oxide, yttrium oxide, and niobium oxide. In parts by weight, the base powder includes 45-55 parts of bauxite powder, 3-5 parts of cordierite powder, 1.5-3.5 parts of kaolin powder, 0.75-1.25 parts of pyrope powder, 28-32 parts of mullite powder, 2.5-3.5 parts of potassium feldspar powder, and 5-8 parts of raw talc powder.

[0004] The Chinese invention patent application with publication number CN115057691A discloses a high-aluminum honeycomb ceramic material resistant to low-concentration hydrofluoric acid corrosion and its preparation method. By introducing raw materials such as barite, zircon sand, and chromium oxide into the formula, the product has good corrosion resistance when the hydrofluoric acid concentration is less than 5%. However, it does not explore the corrosion resistance of ceramic materials in alkaline environments. At the same time, the material has a large shrinkage rate and a high degree of deformation, and parameters such as compressive strength and thermal shock resistance are not characterized. The Chinese invention patent application with publication number CN107892581A discloses a high-strength and corrosion-resistant zirconium corundum honeycomb ceramic body and its preparation method. The high-strength and corrosion-resistant zirconium corundum honeycomb ceramic body prepared by this preparation method can ensure that it has a high operating temperature and high heat capacity, improve its thermal, mechanical properties and corrosion resistance, and significantly extend its service life. However, it only provides the approximate service life of the ceramic, and does not provide specific experimental content and related parameters for the corrosion resistance of the ceramic. The Chinese invention patent application with publication number CN101148355A discloses a method for preparing partially stabilized zirconia ceramics (PSZ) with improved thermal shock resistance. In Example 1, 3 mol% of Y2O3 and ZrO2 powders are added, and in Example 2, 7 mol% of Y2O3 and ZrO2 powders are added. This method can improve the thermal shock resistance of the material. The Chinese invention patent application with publication number CN109706452B discloses a method for preparing a ceramic coating on the surface of high carbon steel. After ball milling a coating raw material containing silicon dioxide powder and aluminum oxide ceramic powder, 1.6-1.7% of rare earth samarium oxide is added, and a binder is added and mixed to obtain a rare earth ceramic coating raw material. The obtained rare earth ceramic coating raw material is coated on the treated high carbon steel surface, and the finished product is obtained after sintering, thereby improving the surface strength and corrosion resistance of the high carbon steel. The preparation process of the ceramic coating is complicated, and no relevant data on its corrosion resistance is displayed. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a thermal shock and corrosion resistant honeycomb ceramic and a preparation method thereof to improve the thermal shock resistance and corrosion resistance of the ceramic in view of the deficiencies in the prior art.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0007] A thermal shock and corrosion resistant honeycomb ceramic comprises a basic powder and a composite additive; the composite additive comprises samarium oxide added in an amount of 1wt%-9wt% of the basic powder and zirconium oxide added in an amount of 1wt%-9wt% of the basic powder.

[0008] At present, there is no related research that adds samarium oxide and zirconium oxide to the raw materials of ceramics in the form of composite additives, and simultaneously improves the thermal shock resistance and corrosion resistance of ceramics through the synergistic effect. On the basis of adding 1w%-9wt% samarium oxide, with the addition of zirconium oxide, the acid and alkali corrosion resistance of the sample gradually improves, and the thermal shock resistance gradually improves.

[0009] In a preferred embodiment of the present invention, the composite additive comprises samarium oxide added in an amount of 1wt%-9wt% of the base powder and zirconium oxide added in an amount of 7wt%-9wt% of the base powder.

[0010] On the basis of adding 1w%-9wt% of samarium oxide, when the addition amount of zirconium oxide is 7wt%-9wt%, the acid and alkali corrosion resistance and thermal shock resistance of the sample can achieve the best effect.

[0011] In a preferred embodiment of the present invention, the composite additive comprises samarium oxide added in an amount of 7wt%-9wt% of the base powder and zirconium oxide added in an amount of 7wt%-9wt% of the base powder.

[0012] When 7%-9wt% of samarium oxide and 7%-9wt% of zirconium oxide are added at the same time, the ceramic has good corrosion resistance and thermal shock resistance. Compared with single addition, the combination of the two can play a synergistic role in corrosion resistance, and the thermal shock resistance is also significantly improved compared to the original sample without additives.

[0013] In a preferred embodiment of the present invention, the base powder comprises the following raw materials in parts by weight: 40-60 parts of bauxite powder, 2-6 parts of cordierite powder, 1-4 parts of kaolin, 0.5-1.5 parts of pyroxene powder, 20-35 parts of mullite powder, 2-4 parts of potassium feldspar, 4-9 parts of raw talc, 2-5‰ of the total mass of the powder as a dispersant, and 0.5-2‰ of the total mass of the powder as a grinding aid.

[0014] In a preferred embodiment of the present invention, the aluminum oxide content of the bauxite powder is >80%;

[0015] The kaolin powder is Suzhou kaolin.

[0016] The present invention also discloses a thermal shock and corrosion resistant honeycomb ceramic, wherein the thermal shock resistance / compressive strength of the thermal shock and corrosion resistant honeycomb ceramic is 129-140 MPa, the weight loss rate after 96 hours of treatment with 98% concentrated sulfuric acid is 0.15-0.21%, the weight loss rate after 96 hours of treatment with 98% concentrated sulfuric acid + 96 hours of treatment with 50% dilute sulfuric acid is 0.96-1.01%, the weight loss rate after 96 hours of treatment with 20% NaOH is 0.08-0.10%, the weight loss rate after 96 hours of treatment with 20% NaOH + 96 hours of treatment with 28% NaOH is 0.28-0.32%; preferably, the true density of the thermal shock and corrosion resistant honeycomb ceramic is 3.43-3.47 g / cm 3 , the linear shrinkage rate is 2.79-3.29%.

[0017] The present invention also discloses a method for preparing a thermal shock-resistant and corrosion-resistant honeycomb ceramic, comprising the following steps:

[0018] S1. Weigh each raw material by weight, and grind it into a ball mill to obtain a mixture;

[0019] S2, adding 1-4% of cellulose by weight of the mixture, 1-3% of palm oil by weight of the mixture, 3-10‰ of polyethylene oxide by weight of the mixture, and 10-20% of deionized water by weight of the mixture to the mixture, and kneading to obtain a kneaded mud segment;

[0020] S3, refining the kneaded mud segment to obtain a refined mud segment;

[0021] S4, pressing the refined mud segment into a desired product using a mold to obtain a wet blank;

[0022] S5, drying the wet blank to obtain a dry blank;

[0023] S6, sintering the dry blank to obtain a finished ceramic product.

[0024] In a preferred embodiment of the present invention, the viscosity of the cellulose in S2 is 80,000-100,000, the palm oil is 28-degree palm oil, and the molecular weight of the polyethylene oxide is 1-8 million.

[0025] In a preferred embodiment of the present invention, the rotation speed of the ball mill in S1 is 10-40 rpm, and the ball milling time is 6-10 hours;

[0026] The kneading speed in S2 is 20-40 rpm, and the kneading time is 10-30 minutes;

[0027] The vacuum degree of refining in S3 is 0.06-0.09;

[0028] The sintering temperature in S6 is 1150°C-1600°C, and the sintering time is 8-9h.

[0029] In a preferred embodiment of the present invention, before S6, the step further includes cutting both ends of the dry blank, and the cutting size is 1-1.20 times the length of the finished ceramic product.

[0030] Compared with the prior art, the present invention has the following beneficial effects: the present invention develops a thermal shock and corrosion resistant honeycomb ceramic and a preparation method thereof, adds a composite additive consisting of samarium oxide and zirconium oxide to the ceramic raw material, synergistically enhances the corrosion resistance of the honeycomb ceramic, ensures the thermal shock resistance of the honeycomb ceramic, and significantly prolongs its service life. The present invention has simple raw material components and low production cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 Schematic diagram of the true density of ceramics with 1%-9% samarium oxide added in the screening experiment of the present invention.

[0032] Figure 2 This is a schematic diagram of the linear shrinkage of ceramics with 1%-9% samarium oxide added in the screening experiment of the present invention.

[0033] Figure 3 This is a schematic diagram of the acid corrosion resistance of ceramics with 1%-9% samarium oxide added in the screening experiment of the present invention.

[0034] Figure 4 This is a schematic diagram of the alkali corrosion resistance of ceramics with 1%-9% samarium oxide added in the screening experiment of the present invention.

[0035] Figure 5 This is a schematic diagram of the compressive strength of ceramics with 1%-9% samarium oxide added in the screening experiment of the present invention.

[0036] Figure 6 This is a schematic diagram of the true density of ceramics with 1%-9% zirconium oxide added in the screening experiment of the present invention.

[0037] Figure 7 This is a schematic diagram of the linear shrinkage of 1%-9% zirconia ceramics added in the screening experiment of the present invention.

[0038] Figure 8 This is a schematic diagram of the acid corrosion resistance of ceramics with 1%-9% zirconium oxide added in the screening experiment of the present invention.

[0039] Fig. 9 This is a schematic diagram of the alkali corrosion resistance of ceramics with 1%-9% zirconium oxide added in the screening experiment of the present invention.

[0040] Fig.10 This is a schematic diagram of the compressive strength of ceramics with 1%-9% zirconium oxide added in the screening experiment of the present invention. DETAILED DESCRIPTION

[0041] In order to verify the effect of different formulas of the above composite additives on the performance improvement of thin-walled honeycomb ceramics, the applicant conducted a series of experimental studies, as follows:

[0042] 1. Effect of samarium oxide addition on ceramic properties

[0043] According to the above method, the raw materials are weighed by weight, 1%-9% samarium oxide is added to the raw materials, and then the raw materials are put into a ball mill, and the ball mill is performed at a speed of 40 revolutions per minute for 10 hours to obtain a mixture; then the mixture is added to a kneading machine, 4% of the mass of the mixture HPMC 100,000 viscosity cellulose, 2% of 28 degree palm oil, 5‰ of 1 million to 8 million molecular weight polyethylene oxide, 15% of deionized water are added, the kneading machine speed is set to 30 revolutions per minute, and kneading is performed for 20 minutes to obtain a kneaded mud segment; the kneaded mud segment is put into a vacuum mud kneading machine, and refined at a vacuum degree of 0.09 to obtain a refined mud segment; the refined mud segment is pressed into a sample for drying, and fired at 1600°C for 3 hours to obtain a thin-walled honeycomb ceramic sample. The true density, linear shrinkage, acid and alkali corrosion resistance and thermal shock resistance of the sample are obtained by the following detection methods.

[0044] (1) True density test: Use a true density measuring instrument to measure the true density of samples with different additive contents;

[0045] (2) Linear shrinkage rate detection: record the dimensions of the sample before and after sintering, compare the dimensional changes before and after sintering, and calculate the linear shrinkage rate of the ceramic;

[0046] (3) Acid corrosion test: One group of samples was placed in a 98% dilute sulfuric acid solution and stirred at room temperature (25°C) for 96 hours using a magnetic stirrer with a speed set to 450 rpm. The samples were taken out and dried, and the mass loss rate was measured. Another group of samples was placed in a 50% dilute sulfuric acid solution and stirred for 96 hours. The samples were then placed in a 50% dilute sulfuric acid solution and stirred for 96 hours. The samples were taken out and dried, and the mass loss rate was measured. The acid corrosion resistance of the samples was characterized by the mass loss rate.

[0047] (4) Alkali corrosion resistance test: One group of samples was placed in a 20% sodium hydroxide solution and stirred at room temperature (25°C) for 96 hours using a magnetic stirrer with a speed set to 450 rpm. The mass loss rate of the samples was measured after the samples were taken out and dried. Another group of samples was placed in a 20% sodium hydroxide solution and stirred for 96 hours. The samples were then placed in a 28% sodium hydroxide solution and stirred for 96 hours. The mass loss rate of the samples was measured after the samples were taken out and dried. The alkali corrosion resistance of the samples was characterized by the mass loss rate.

[0048] (5) Thermal shock resistance test: The ceramic samples were heated to 800°C in a high-temperature furnace and then quickly transferred to cold water at 25°C for cooling. After repeated thermal cycles for 5 times, the samples were subjected to a compressive strength test and compared with the compressive strength of samples that had not undergone thermal cycles at room temperature to evaluate their thermal shock resistance.

[0049] Figure 1 is the true density of ceramics with different samarium oxide addition amounts. Figure 2 Linear shrinkage of ceramics with different samarium oxide addition amounts. Figure 3 Acid corrosion resistance of ceramics with different samarium oxide addition amounts. Figure 3 (a) Acid corrosion resistance condition: 98% concentrated sulfuric acid treatment for 96 hours, Figure 3 (b) Acid corrosion resistance conditions are 98% concentrated sulfuric acid treatment for 96 hours + 50% dilute sulfuric acid treatment for 96 hours.

[0050] Figure 4 Alkali corrosion resistance of ceramics with different samarium oxide addition amounts. Figure 4 (a) Alkali corrosion resistance condition is 20% NaOH treatment for 96 hours, Figure 4 (b) Alkali corrosion resistance conditions are 20% NaOH treatment for 96 hours + 28% NaOH treatment for 96 hours. Figure 5 Thermal shock resistance of ceramics with different samarium oxide addition amounts.

[0051] Depend on Figure 1 , Figure 2 , Figure 3 , Figure 4 , Figure 5 It can be seen that with the increase of samarium oxide addition, the true density of the sample gradually increases, the linear shrinkage rate gradually increases, and the mass loss rate after immersion in acidic and alkaline solutions shows a downward trend, indicating that its acid and alkali corrosion resistance gradually improves; among them, when the samarium oxide addition amount is 7%-9%, the effect is the best. However, at this time, the corresponding sample has a high degree of shrinkage and deformation, and the thermal shock resistance is average, so it is necessary to consider combining other additives to further optimize the ceramic performance.

[0052] 2. Effect of zirconium oxide addition on ceramic properties

[0053] According to the above method, the raw materials are weighed by weight, 1%-9% of zirconium oxide is added to the raw materials, and then the raw materials are put into a ball mill, and the ball mill is performed at a speed of 40 revolutions per minute for 10 hours to obtain a mixture; then the mixture is added to a kneading machine, 4% of the mass of the mixture HPMC 100,000 viscosity cellulose, 2% of 28 degree palm oil, 5‰ of 1 million to 8 million molecular weight polyethylene oxide, 15% of deionized water are added, the kneading machine speed is set to 30 revolutions per minute, and kneading is performed for 20 minutes to obtain a kneaded mud segment; the kneaded mud segment is put into a vacuum mud kneading machine, and refined at a vacuum degree of 0.09 to obtain a refined mud segment; the refined mud segment is pressed into a sample for drying, and fired at 1600°C for 3 hours to obtain a thin-walled honeycomb ceramic sample. The true density, linear shrinkage, acid and alkali corrosion resistance and thermal shock resistance of the sample are obtained by the following detection methods.

[0054] (1) True density test: Use a true density measuring instrument to measure the true density of samples with different additive contents;

[0055] (2) Linear shrinkage rate detection: record the dimensions of the sample before and after sintering, compare the dimensional changes before and after sintering, and calculate the linear shrinkage rate of the ceramic;

[0056] (3) Acid corrosion test: One group of samples was placed in a 98% dilute sulfuric acid solution and stirred at room temperature (25°C) for 96 hours using a magnetic stirrer with a speed set to 450 rpm. The samples were taken out and dried, and the mass loss rate was measured. Another group of samples was placed in a 50% dilute sulfuric acid solution and stirred for 96 hours. The samples were then placed in a 50% dilute sulfuric acid solution and stirred for 96 hours. The samples were taken out and dried, and the mass loss rate was measured. The acid corrosion resistance of the samples was characterized by the mass loss rate.

[0057] (4) Alkali corrosion resistance test: One group of samples was placed in a 20% sodium hydroxide solution and stirred at room temperature (25°C) for 96 hours using a magnetic stirrer with a speed set to 450 rpm. The mass loss rate of the samples was measured after the samples were taken out and dried. Another group of samples was placed in a 20% sodium hydroxide solution and stirred for 96 hours. The samples were then placed in a 28% sodium hydroxide solution and stirred for 96 hours. The mass loss rate of the samples was measured after the samples were taken out and dried. The alkali corrosion resistance of the samples was characterized by the mass loss rate.

[0058] (5) Thermal shock resistance test: The ceramic samples were heated to 800°C in a high-temperature furnace and then quickly transferred to cold water at 25°C for cooling. After repeated thermal cycles for 5 times, the samples were subjected to a compressive strength test and compared with the compressive strength of samples that had not undergone thermal cycles at room temperature to evaluate their thermal shock resistance.

[0059] Figure 6 True density of ceramics with different zirconium oxide addition amounts. Figure 7 Linear shrinkage of ceramics with different zirconium oxide addition amounts. Figure 8 Acid corrosion resistance of ceramics with different zirconium oxide addition amounts. Figure 8 (a) Acid corrosion resistance condition: 98% concentrated sulfuric acid treatment for 96 hours, Figure 8 (b) Acid corrosion resistance conditions are 98% concentrated sulfuric acid treatment for 96 hours + 50% dilute sulfuric acid treatment for 96 hours. Fig. 9 Alkali corrosion resistance of ceramics with different zirconium oxide addition amounts. Fig. 9 (a) Alkali corrosion resistance condition is 20% NaOH treatment for 96 hours, Fig. 9 (b) Alkali corrosion resistance conditions are 20% NaOH treatment for 96 hours + 28% NaOH treatment for 96 hours.

[0060] Fig.10 Thermal shock resistance of ceramics with different zirconia addition amounts.

[0061] Depend on Figure 6 , Figure 7 , Figure 8 , Fig. 9 , Fig.10 It can be seen that with the increase of zirconium oxide addition, the true density of the sample gradually increases, the linear shrinkage rate gradually decreases, and the overall sample shows a trend of change from inward contraction to outward expansion. Although the mass loss rate after immersion in acidic and alkaline solutions shows a downward trend, its effect on the corrosion resistance of ceramics is smaller than that of samarium oxide. With the increase of zirconium oxide addition, the compressive strength of the corresponding sample gradually increases after 5 thermal cycles, indicating that the addition of zirconium oxide can significantly enhance the thermal shock resistance of ceramics. This is because zirconium oxide transforms from tetragonal phase to monoclinic phase during the cooling process, causing volume expansion and compensating for part of the firing shrinkage. At the same time, diffusely distributed microcracks are generated in the matrix. These tiny cracks cause the extension direction of the main crack to bifurcate or change, effectively hindering the expansion and extension of the cracks, thereby improving the toughness and indirectly improving the thermal shock resistance.

[0062] Therefore, based on the above comparative experiments, it is considered to add an appropriate amount of zirconium oxide on the basis of adding 7%-9% of samarium oxide, so as to obtain honeycomb ceramics with good thermal shock resistance and corrosion resistance.

[0063] 3. Effect of adding 7%-9% samarium oxide and 1%-9% zirconium oxide on ceramic properties

[0064] According to the above method, samples were prepared, and the true density, linear shrinkage, acid and alkali corrosion resistance and thermal shock resistance of the samples were tested. Table 1 shows the performance parameters of the samples prepared with different amounts of samarium oxide and zirconium oxide added.

[0065] Table 1 Performance parameters of samples prepared with different amounts of samarium oxide and zirconium oxide added

[0066]

[0067] Combined with Table 1, it can be seen that when the amount of samarium oxide added is constant, as the amount of zirconium oxide added increases, the true density of the sample gradually increases, and the linear shrinkage gradually decreases. When the amount of zirconium oxide added is in the range of 7%-9%, the sintering deformation of the sample is the smallest. At the same time, with the addition of zirconium oxide, the acid and alkali corrosion resistance of the sample gradually improves, and the thermal shock resistance gradually improves. The best effect can be achieved when the amount of zirconium oxide added is 7%-9%.

[0068] Combined with the experimental results of single additives, it can be seen that compared with the single addition of 7%-9% samarium oxide or 7%-9% zirconium oxide, when 7%-9% samarium oxide and 7%-9% zirconium oxide are added at the same time, the ceramic has good corrosion resistance and thermal shock resistance. Compared with the single addition, the combination of the two can play a synergistic role in corrosion resistance, and the thermal shock resistance is also significantly improved compared to the original sample without additives.

[0069] Example 1

[0070] A heat shock and corrosion resistant honeycomb ceramic is prepared from the following raw materials in parts by weight (kg): 50 parts of bauxite powder with an aluminum oxide content of more than 80%, 3 parts of cordierite powder, 2 parts of Suzhou kaolin, 0.5 parts of pyrope powder, 25 parts of mullite powder, 3.5 parts of potassium feldspar, 4 parts of raw talc, 5‰ of the total weight of the powder as a dispersant, 2‰ of the total weight of the powder as a grinding aid, 8% of the total weight of the powder as samarium oxide and 7% of the total weight of the powder as zirconium oxide.

[0071] A method for preparing a thermal shock-resistant and corrosion-resistant honeycomb ceramic comprises the following steps:

[0072] (1) Weighing each raw material by weight, placing the raw material into a ball mill, and ball milling at a speed of 20 revolutions per minute for 9 hours to obtain a mixed material;

[0073] (2) adding the mixture to a kneader, adding 2% of the mass of the mixture HPMC 100,000 viscosity cellulose, 2% of 28 degree palm oil, 8‰ of 5 million molecular weight polyethylene oxide, and 15% of deionized water, setting the kneader speed to 30 revolutions per minute, and kneading for 20 minutes to obtain a kneaded mud segment;

[0074] (3) putting the kneaded mud segment into a vacuum mud kneading machine and refining it at a vacuum degree of 0.08 to obtain a refined mud segment;

[0075] (4) using a mold to press into a desired product to obtain a wet blank;

[0076] (5) drying the wet blank to obtain a dry blank;

[0077] (6) cutting the two ends of the dry blank, the cutting size is 1-1.20 times the length of the finished product, and obtaining a cut dry blank;

[0078] (7) The cut dry blank is placed in a kiln and fired at 1150°C to obtain a finished product.

[0079] The performance indicators of the finished ceramic products, such as true density, linear shrinkage, acid and alkali corrosion resistance and thermal shock resistance, are tested, as shown in Table 2.

[0080] Table 2 Performance of ceramic finished product obtained in Example 1

[0081]

[0082] Example 2

[0083] A thermal shock and corrosion resistant honeycomb ceramic is prepared from the following raw materials in parts by weight (kg): 50 parts of bauxite powder with an aluminum oxide content of more than 80%, 3 parts of cordierite powder, 2 parts of Suzhou kaolin, 0.5 parts of pyrope powder, 25 parts of mullite powder, 3.5 parts of potassium feldspar, 4 parts of raw talc, 5‰ of the total weight of the powder as a dispersant, 2‰ of the total weight of the powder as a grinding aid, 8% of the total weight of the powder as samarium oxide and 9% of the total weight of the powder as zirconium oxide.

[0084] A method for preparing a thermal shock-resistant and corrosion-resistant honeycomb ceramic comprises the following steps:

[0085] (1) Weighing each raw material by weight, placing the raw material into a ball mill, and ball milling at a speed of 20 revolutions per minute for 9 hours to obtain a mixed material;

[0086] (2) adding the mixture to a kneader, adding 2% of the mass of the mixture HPMC 100,000 viscosity cellulose, 2% of 28 degree palm oil, 8‰ of 5 million molecular weight polyethylene oxide, and 15% of deionized water, setting the kneader speed to 30 revolutions per minute, and kneading for 20 minutes to obtain a kneaded mud segment;

[0087] (3) putting the kneaded mud segment into a vacuum mud kneading machine and refining it at a vacuum degree of 0.08 to obtain a refined mud segment;

[0088] (4) using a mold to press into a desired product to obtain a wet blank;

[0089] (5) drying the wet blank to obtain a dry blank;

[0090] (6) cutting the two ends of the dry blank, the cutting size is 1-1.20 times the length of the finished product, and obtaining a cut dry blank;

[0091] (7) The cut dry blank is placed in a kiln and fired at 1150°C to obtain a finished product.

[0092] The performance indicators of the finished ceramic products, such as true density, linear shrinkage, acid and alkali corrosion resistance and thermal shock resistance, are tested, as shown in Table 3.

[0093] Table 3 Performance of ceramic finished product obtained in Example 2

[0094]

[0095] Example 3

[0096] A thermal shock and corrosion resistant honeycomb ceramic is prepared from the following raw materials in parts by weight (kg): 50 parts of bauxite powder with an aluminum oxide content of more than 80%, 3 parts of cordierite powder, 2 parts of Suzhou kaolin, 0.5 parts of pyrope powder, 25 parts of mullite powder, 3.5 parts of potassium feldspar, 4 parts of raw talc, 5‰ of the total weight of the powder as a dispersant, 2‰ of the total weight of the powder as a grinding aid, 8% of the total weight of the powder as samarium oxide and 8% of the total weight of the powder as zirconium oxide.

[0097] A method for preparing a thermal shock-resistant and corrosion-resistant honeycomb ceramic comprises the following steps:

[0098] (1) Weighing each raw material by weight, placing the raw material into a ball mill, and ball milling at a speed of 20 revolutions per minute for 9 hours to obtain a mixed material;

[0099] (2) adding the mixture to a kneader, adding 2% of the mass of the mixture HPMC 100,000 viscosity cellulose, 2% of 28 degree palm oil, 8‰ of 5 million molecular weight polyethylene oxide, and 15% of deionized water, setting the kneader speed to 30 revolutions per minute, and kneading for 20 minutes to obtain a kneaded mud segment;

[0100] (3) putting the kneaded mud segment into a vacuum mud kneading machine and refining it at a vacuum degree of 0.08 to obtain a refined mud segment;

[0101] (4) using a mold to press into a desired product to obtain a wet blank;

[0102] (5) drying the wet blank to obtain a dry blank;

[0103] (6) cutting the two ends of the dry blank, the cutting size is 1-1.20 times the length of the finished product, and obtaining a cut dry blank;

[0104] (7) The cut dry blank is placed in a kiln and fired at 1150°C to obtain a finished product.

[0105] The performance indicators of the finished ceramic products, such as true density, linear shrinkage, acid and alkali corrosion resistance and thermal shock resistance, are tested, as shown in Table 4.

[0106] Table 4 Performance of ceramic finished product obtained in Example 3

[0107]

[0108] The above embodiments are intended to illustrate the present invention, not to limit the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only intended to illustrate the specific working principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which shall all fall within the scope of the present invention to be protected. The scope of protection of the present invention shall be defined by the attached claims and their equivalents.

Claims

1. A thermal shock and corrosion resistant honeycomb ceramic, characterized in that: It comprises a basic powder and a composite additive; the composite additive comprises samarium oxide whose addition amount is 1wt%-9wt% of the basic powder and zirconium oxide whose addition amount is 1wt%-9wt% of the basic powder.

2. The thermal shock and corrosion resistant honeycomb ceramic according to claim 1, characterized in that: The composite additive includes samarium oxide added in an amount of 1 wt% to 9 wt% of the base powder and zirconium oxide added in an amount of 7 wt% to 9 wt% of the base powder.

3. The thermal shock and corrosion resistant honeycomb ceramic according to claim 2, characterized in that: The composite additive includes samarium oxide added in an amount of 7wt%-9wt% of the base powder and zirconium oxide added in an amount of 7wt%-9wt% of the base powder.

4. The thermal shock and corrosion resistant honeycomb ceramic according to claim 1, characterized in that: The base powder comprises the following raw materials in parts by weight: 40-60 parts of bauxite powder, 2-6 parts of cordierite powder, 1-4 parts of kaolin, 0.5-1.5 parts of pyrope powder, 20-35 parts of mullite powder, 2-4 parts of potassium feldspar, 4-9 parts of raw talc, 2-5‰ of the total weight of the powder as a dispersant, and 0.5-2‰ of the total weight of the powder as a grinding aid.

5. The thermal shock and corrosion resistant honeycomb ceramic according to claim 4, characterized in that: The aluminum oxide content of the bauxite powder is greater than 80%; The kaolin powder is Suzhou kaolin.

6. A thermal shock and corrosion resistant honeycomb ceramic, characterized in that: The thermal shock resistance / compressive strength of the thermal shock and corrosion resistant honeycomb ceramic is 129-140MPa, the weight loss rate after 96 hours of treatment with 98% concentrated sulfuric acid is 0.15-0.21%, the weight loss rate after 96 hours of treatment with 98% concentrated sulfuric acid + 96 hours of treatment with 50% dilute sulfuric acid is 0.96-1.01%, the weight loss rate after 96 hours of treatment with 20% NaOH is 0.08-0.10%, and the weight loss rate after 96 hours of treatment with 20% NaOH + 96 hours of treatment with 28% NaOH is 0.28-0.32%; preferably, the true density of the thermal shock and corrosion resistant honeycomb ceramic is 3.43-3.47g / cm 3 The linear shrinkage rate of the heat shock and corrosion resistant honeycomb ceramic is 2.79-3.29%.

7. A method for preparing the thermal shock and corrosion resistant honeycomb ceramic according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Weigh each raw material by weight, and grind it into a ball mill to obtain a mixture; S2, adding 1-4% of cellulose by weight of the mixture, 1-3% of palm oil by weight of the mixture, 3-10‰ of polyethylene oxide by weight of the mixture, and 10-20% of deionized water by weight of the mixture to the mixture, and kneading to obtain a kneaded mud segment; S3, refining the kneaded mud segment to obtain a refined mud segment; S4, pressing the refined mud segment into a desired product using a mold to obtain a wet blank; S5, drying the wet blank to obtain a dry blank; S6, sintering the dry blank to obtain a finished ceramic product.

8. The preparation method according to claim 7, characterized in that: The viscosity of the cellulose in S2 is 80,000-100,000, the palm oil is 28-degree palm oil, and the molecular weight of the polyethylene oxide is 1-8 million.

9. The preparation method according to claim 7, characterized in that: The ball milling speed in S1 is 10-40 rpm, and the ball milling time is 6-10 hours; The kneading speed in S2 is 20-40 rpm, and the kneading time is 10-30 minutes; The vacuum degree of refining in S3 is 0.06-0.09; The sintering temperature in S6 is 1150°C-1600°C, and the sintering time is 8-9h.

10. The preparation method according to claim 7, characterized in that: Before S6, the process also includes cutting two ends of the dry blank, wherein the cutting size is 1-1.20 times the length of the finished ceramic product.

Citation Information

Patent Citations

  • Method for preparing partial stabilization zirconium oxide ceramic capable of increasing thermal shock resistance

    CN101148355A

  • High-strength anti-corrosion zirconia-corundum honeycomb ceramic body and preparation method thereof

    CN107892581A

  • A method for preparing ceramic coatings on high carbon steel surfaces

    CN109706452B

  • High-aluminum honeycomb ceramic material resistant to corrosion of low-concentration hydrofluoric acid and preparation method of high-aluminum honeycomb ceramic material

    CN115057691A

  • Honeycomb ceramic heat accumulator and preparation method thereof

    CN117362070A

Cited By

  • Thin-wall honeycomb ceramic with thermal shock resistance and mechanical property and preparation method of thin-wall honeycomb ceramic

    CN119613095A

  • Thin-walled honeycomb ceramic with both thermal shock resistance and mechanical properties and preparation method thereof

    CN119613095B